Monitoring acute effects on athletic performance with mixed linear modeling - Vandenbogaerde, T. J.; Hopkins, W. G. (Medicine & Science in Sports & Exercise, 2010)
There is a need for a sophisticated approach to track athletic performance and to quantify factors affecting it in practical settings.